Investigation of oscillations in katabatic Prandtl slope flows. (16th December 2022) - Henao‐Garcia, Sebastian; Xiao, Cheng‐Nian; Senocak, Inanc
Abstract: Dynamically unstable katabatic Prandtl slope flows are studied via numerical simulations and spectral analysis. Results confirm the presence of aperiodic temporal and spatial oscillations in the flow fields due to the emergence and propagation of flow instabilities. Damped en masse oscillations are observed to dominate the initial oscillatory stage of laminar katabatic slope flows. Stationary longitudinal rolls, which are dominant at shallow slopes, are observed to meander with increasing stratification perturbation parameter and the average distance between the rolls exhibits a strong dependence on slope inclination for slope angles less than 3 5 ∘ $$ 3{5}^{° } $$ . At much steeper slopes, traveling slope waves emerge and they are transported at the mean jet velocity. Both types of instability rolls coexist for certain combinations of dimensionless parameters, forming intricate structures that break into smaller eddies as the flow becomes more dynamically unstable. In the dynamically unstable nonturbulent regime, en masse oscillations are insignificant, but their normalised frequency can be used to discern the type of flow instability. Abstract : Katabatic Prandtl slope flows in dynamically unstable, yet nonturbulent regimes are investigated numerically. The results confirm the presence of aperiodic temporal and spatial oscillations in the flow fields that are associated with the emergence and propagation of flow instabilities. Contrary to the situation in turbulent slope flows, en masse oscillations are insignificant in this dynamically unstable regime dominated by large‐scale vortex structures, but the normalised en masse oscillation frequency could serve as a metric to discern the type of instability.